Pengujian Biologis Makanan Bayi dengan Bahan Pokok Sagu dan Tepung Tempe Terhadap Pertambahan Berat Badan Tikus Putih (Rattus norvegicus) - Titiek F. Djaafar; Agnes Murdiati; Indyah S. Utami (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1995)
A formulation of infant food made from mixture of sago Strach, tempeh flour, milk powder and corn oil gave a normal body weight of the growth of rates at normal physical conditions relating to the activities, hairs skin, eye colour and tail colour. The total feed intake individual macronutrient of the ingredients increased the body weight, which fitted the multiple regression equation: Y =-38,57 + 0,37 x1 + 0,75 x2 - 4,08 x3, - 2,60 x4+ 1,71 x5. By using this equation, a certain body weight might be reached by manipulating the X variables. The increase In body weight was significantly dependent on the quantity and quality of protein intake.